MIKROHABITAT DAN POLA PERUSAKAN DAUN OLEH SERANGGA FITOFAGUS KUMBANG KURA-KURA (Aspidomorpha sanctaecrucis F. dan Aspidomorpha miliaris F.) PADA TANAMAN KANGKUNG PAGAR (Ipomoea carnea) - Eladisa Ganjari, Leo (Widya Warta, 2019)
Ganjari’s study 2014), found two species of turtle beetles (Aspidomorpha sanctaecrucis F. and Aspidomorpha miliaris F)  lived on the fence-water spinach (Ipomoea carnea). By finding them on the fence-water spinach the researcher wanted to phytophage insects live in microhabitat and to find out the potternaf leaves damage. The purpose of  the  study was to find out answers of the problems formulated. The method use wle beettles as  by observasing two mature of  turtle beetles in the isolation cages. The conclusion of the study found that  dimensional microhabitat in the turtle betles species that live on the on the fence-water spinach was overlapped . the pottern of leaves damages of the two species was different character. The pottern of leaves damages of Aspidomorpha sanctaecrucis F, could be seen from the edge of the leaves while the pottern of leaves demages of Aspidomorpha miliaris F could be seen from the middle of the leaves.